DEVELOPMENT OF EMOTIONAL AND WILL-QUALITIES OF CHILDREN IN SPORTS - Fayzullayev Sherzod Bahodirovich; Sharafitdinov Abdulla XXX (Journals Park Publishing, 2022)
This article describes the socio-psychological features of the development of the athlete's personality and their emotional and volitional qualities. In the formation of volitional qualities, the individual aspects of decision-making and its implementation are highlighted. Conclusions and recommendations are given on the development of moral and volitional qualities in children, the further development of mental processes.
Keywords: Will; willpower; willpower activity